CHARACTERISTICS OF MACROZOOBENTHOS COMMUNITY WITH SUBSTRATES TYPE AT WARKUK RIVER DISTRICK OF WARKUK RANAU SELATAN, OKU SELATAN REGENCY, SOUTH SUMATERA - Hamudin, Frianti; Fauziah, -; Hanafiah, Zazili (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2016)
The research about Characteristic of Macrozoobenthos Community With Substrates Type At Warkuk River Districk of Warkuk Ranau Selatan, OKU Selatann Regency, South Sumatera has been conducted from May 2013 to December 2015. This study aims to analysis of characteristic and makrozoobenthos composition in substrat type, analysis about physic and chemistry condition at Warkuk River. Determination of sampling sites were conducted by Random Sampling. The Sample of macrozoobenthos were identified at the Laboratory of Research Institute for Inland Fisheries Mariana, Palembang. From the results obtained, are grouped into 3 classes of macrozoobenthos namely Insecta, Gastropoda and Oligochaeta, which is classified into 9 orders consists of 14 families, 16 spesies. Density ranging from 1155,56 to 1755,56 individuals/m2. Level of diversity are high, ranging from 1,95 to 2,41 and dominance index ranging from 0,31 to 0,40. Family Biotic Index (FBI) ranging from 3,47 to 3,98 with the water quality category of excellent.Key words : Warkuk River, Macrozoobenthos, Substrat Type